1974
DOI: 10.1017/s0022143000023431
|View full text |Cite
|
Sign up to set email alerts
|

Radio-Frequency Interferometry—A new technique For studying glaciers

Abstract: ABSTRACT. A new method of electromagnetic sounding in resistive electrical environments has been developed for use in lunar exploration. It is applicable to the study of terrestrial glaciers and ice sheets. A horizontal electric dipole antenna on the ground is used to transmit power at frequencies of 1,2,4,8, 16 and 32 MHz. A set of orthogonal receiving coils is mounted on a vehicle which traverses away from the transmitter. Field strength is recorded as a function of distance. Waves which travel above the sur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

1976
1976
1998
1998

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(10 citation statements)
references
References 3 publications
0
10
0
Order By: Relevance
“…These results seem to be at odds with the experimental results of Strangway and others (1974). Their continuous-wave experiment indicated that scattering was strong at freequencies as low as 8 MHz.…”
Section: The Scatterersmentioning
confidence: 73%
See 2 more Smart Citations
“…These results seem to be at odds with the experimental results of Strangway and others (1974). Their continuous-wave experiment indicated that scattering was strong at freequencies as low as 8 MHz.…”
Section: The Scatterersmentioning
confidence: 73%
“…It. is quite clear freom Figure 5 that a Gaussian distribution of scatterer radii with a mean radius of about 1.0 m and a standard gerviation of 0.2 to 0.4 m explains the scattering observations of Strangway and others (1974). Scattering is uniformly strong at freequencies of 16 MHz and higher, intermediate at 8 MHz, and weak at 4 MHz and below.…”
Section: The Scatterersmentioning
confidence: 77%
See 1 more Smart Citation
“…To date, the interferometric approach has not received much favour and, compared to radar sounding, it does not seem to be a particularly good method of measuring ice thickness. Rossiter and others (1973) and Strangway and others (1974), without apparently knowing of Stern's work, revived the method in an interesting application. A multi-frequency interferometer (1-32 MHz) was developed for studying the lunar surface and field tested on Athabasca Glacier and Gornergletscher.…”
Section: Geophysical Measurementsmentioning
confidence: 99%
“…Also, several low-frequency RES systems were developed specifically for sounding temperate glaciers where absorption losses arc significant due to higher ice temperatures and the presence of liquid water. Systems with frequencies of 1-32 MHz have been successfully used by numerous researchers to sound temperate glaciers (Strangway and others, 1974; Watts and England, 1976; Bjornsson and others, 1977; Sverrisson and others, 1980; Watts and Wright, 1981).…”
Section: Introductionmentioning
confidence: 99%